Terphenyl backbone-based donor–π–acceptor dyads: geometric isomer effects on intramolecular charge transfer. Issue 6 (24th January 2020) - Kim, Min-Ji; Ahn, Mina; Shim, Jun Ho; Wee, Kyung-Ryang
Abstract : The molecular geometry effects of ortho, meta, and para -terphenyl based donor–π–acceptor (D–π–A) dyads on intramolecular charge transfer (ICT) were studied to investigate structure-ICT relationships. Abstract : The molecular geometry effects of ortho, meta, and para -terphenyl based donor–π–acceptor (D–π–A) dyads on intramolecular charge transfer (ICT) were studied to investigate structure-ICT relationships. Terphenyl based D–π–A dyads were prepared by two-step palladium catalyzed, Suzuki–Miyaura coupling reactions, in which triphenylamine (TPA) was used as the electron donor and 1, 2-diphenyl-benzimidazole (IMI) as the electron acceptor. The photophysical and electrochemical properties of terphenyl backbone-based ortho (O ), meta (M ), and para (P ) dyads were compared. In steady state absorption spectra, a red-shift of CT band was observed in the order O < M < P, which was attributed to terphenyl isomer conjugation effects and agreed well with density functional theory (DFT) based calculations. In particular, the emission spectra of the three terphenyl D–π–A dyads produced showed similar emission maxima at ∼475 nm and a bathochromic shift property was observed in order to increase the solvent polarity, indicating the ICT process. From Lippert–Mataga plots, excited-state dipole moment changes (Δ μ ) were estimated to be 31.5 Debye (D) for O, 62.9 D for M, and 51.5 D for P . For M isomer, a large Δ μ and the markedly reduced quantum yield was shown, as well as photo-induced electron transfer (PET) was expected in the excited state, but no radical species were observed by femtosecond transient absorption (TA) measurements. Based on experimental results, we conclude that all three terphenyl based D–π–A dyads, including non-conjugated ortho - and meta -terphenyl dyads, exhibit partial charge transfer rather than unit-electron transfer.